A Closer Look at the Output Hypothesis: The Effect of Pushed Output on Noticing and Inductive Learning of the Spanish Future Tense. (20th February 2014) - Russell, Victoria
Abstract This study empirically tested the noticing function of the output hypothesis (Swain, 1993, 1995, 1998) and explored the relationship between noticing and learning by comparing the effects of the production of output to exposure to textually enhanced input. The present study is a conceptual replication of Izumi (2002); however, Izumi examined a complex grammatical form (relativization in English) while the present study investigated a more salient form (the Spanish future tense) among 55 first‐semester students of Spanish. The results supported the noticing function of the output hypothesis and revealed that pushed output followed by exposure to future tense forms in subsequent input enabled students to learn the targeted form inductively. However, exposure to textual enhancement did not produce similar learning gains. These findings have implications for the instruction of second language grammar.